Spectrum of neuroendocrine neoplasms of GIT – a histomorphological study in a tertiary care centre - Muralidhar, Aparna; Mahadevan, Pushpa (Journal of Medical Science, 2023)
Background. Neuroendocrine neoplasms are diverse in terms of sites of origin, functional status, and degrees of aggressiveness. Since neuroendocrine cells are ubiquitous in the human body, these neoplasms can arise in different organs, with gastrointestinal tract being most frequently involved. The past few years have seen a surge in the diagnosis of these neoplasms, which were earlier considered to be rare. Their nomenclature, classification, and diagnostic criteria are revamped frequently, as new knowledge emerges.Aim. To study the histopathological spectrum of neuroendocrine neoplasms of gastrointestinal tract and assess the immunohistochemical expression of neuroendocrine markers in them.Material and methods. Ours is a descriptive study of the distribution and pathologic characteristics of gastrointestinal neuroendocrine neoplasms in a tertiary care hospital in Kerala, over a three year period. Neoplasms were categorised based on 2019 updated WHO classification.Results. Among the 59 cases, we observed a male predominance. (Male to female ratio - 1.8:1). Most patients were in 6th and 7th decades of life. Duodenum was most frequently involved followed by rectum and appendix. NET G2 and G1 constituted the predominant histologic grades (47% and 24% respectively). NEC and MiNEN were infrequent. All cases were positive for synaptophysin, with variable positivity for chromogranin. Ki67 helped establish the histologic grade. We also came across a rare case of neuroendocrine tumor with coexisting mucinous neoplasm in appendix.Conclusions. With evolving knowledge and advanced imaging modalities, the incidence of these neoplasms is increasing with time.  Histopathology is the mainstay of diagnosis and plays a decisive role in influencing management protocols and prognosis.